THE IMPLEMENTATION ANALYSIS OF FAIR TRADE AS AN IDEAL MODEL FOR CORPORATE SOCIAL RESPONSIBILITY (A CASE STUDY AT PT KIMIA FARMA) - Azky Hudaya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Fair Trade is an ideal model of Corporate Social Responsibility implementation, because of the principles contained in the trade fair were able to give an impact for the long term not only for the company, but also gives sustainability to the social conditions of people and environment. Fair Trade is an alternative trade movement that is fighting for their guarantee of a fair purchase price, while improving social and environmental conditions for community producers. This study aims to give evidence about the implementation of fair trade by companies in Indonesia and whether the impact of the fair trade to the company. This explanatory research will explain the impact of fair trade practices that have been carried out by the company in Indonesia. This study conducted through qualitative approach and content analysis method by conducting an analysis of the annual reports, media reports, journals, articles, awards obtained by company, and the results of other relevant or previous studies. In analyzing fair trade practice, researchers conducted a cross-check using the 10 principles of fair trade that has been created and defined by the World Fair Trade Organization (WFTO) as an official institution that lead the fair trade movement worldwide with the object of research on the company PT Kimia Farma which is a largest state-owned company operating in the pharmaceutical sector. Results of research shows that PT. Kimia Farma has been running its operations based on the principles of fair trade although there are two principles not found information. This shows that one company in Indonesia has adopted the practice of fair trade although there is no written evidence or certification of fair trade in the company and acceptable impact companies that implement fair trade practices, fair trade practice impact the company net profit level on year 2011-2015.Keywords: Corporate Social Responsibility, Fair Trade, Alternative Trade Movement